Campus Canopy, 1938-03-05 - The Campus Canopy, The Georgia State Woman's College (Georgia State Womans College, 1938)
Holidays and Exams -- Freshman and Juniors Swing out At Annual Formal Dance to Music of Curtis Davidson's Orchestra -- Virginia Zipplies Will Reign At MAy Festival; Bunn Is Maid of Honor
Georgia State Womans College Student Newspaper
Keywords: Valdosta State University -- Periodicals